2019
DOI: 10.1029/2019gl083071
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Electron Acceleration in Low‐Density Regions of Saturn's Radiation Belt by Whistler Mode Chorus Waves

Abstract: Electron acceleration at Saturn due to whistler mode chorus waves has previously been assumed to be ineffective; new data closer to the planet show it can be very rapid (factor of 104 flux increase at 1 MeV in 10 days compared to factor of 2). A full survey of chorus waves at Saturn is combined with an improved plasma density model to show that where the plasma frequency falls below the gyrofrequency additional strong resonances are observed favoring electron acceleration. This results in strong chorus acceler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 32 publications
2
34
0
Order By: Relevance
“…Roussos et al (2018) demonstrated that transport time scales from the middle magnetosphere to Saturn's electron radiation belts due to time-variable electric fields with a fixed local time pattern are on the order of 1-2 weeks. A competing process of wave-driven acceleration requires time scales of ∼ 1 day (Woodfield Glauert et al, 2019) around L = 5 to ∼100 days (Woodfield Horne et al, 2018) much further in. The convection and wave acceleration time scales are comparable at L > 5.…”
Section: Resultsmentioning
confidence: 99%
“…Roussos et al (2018) demonstrated that transport time scales from the middle magnetosphere to Saturn's electron radiation belts due to time-variable electric fields with a fixed local time pattern are on the order of 1-2 weeks. A competing process of wave-driven acceleration requires time scales of ∼ 1 day (Woodfield Glauert et al, 2019) around L = 5 to ∼100 days (Woodfield Horne et al, 2018) much further in. The convection and wave acceleration time scales are comparable at L > 5.…”
Section: Resultsmentioning
confidence: 99%
“…At L < 4 R S in Saturn’s magnetosphere, Woodfield et al. (2019) proposed that the acceleration of electrons to relativistic energies by whistler waves may lead to the butterfly PADs observed at L ∼ 3 R S (Paranicas, Mitchell, Krimigis, et al., 2010). It has also been shown that there are intense Z‐mode waves in this area (Menietti et al., 2015, 2016; Ye et al., 2010).…”
Section: Discussion: Pad Inward Of L = 4 Rs and The Implication On Rementioning
confidence: 99%
“…As discussed by Horne and Thorne (1998) and Glauert and Horne (2005), Z-mode can efficiently scatter electrons similar to whistler-mode chorus. This emission has been studied at Saturn by Ye et al (2010), Gu et al (2013), and Menietti et al (2015), and modeled at Saturn by E. E. Woodfield et al (2018Woodfield et al ( , 2019. Source regions for narrowband Z-mode at Saturn are not well understood, but may be near density gradients along the inner edge of the Enceladus torus and near the ring plane in the inner magnetosphere, as well as near Saturn kilometric radiation source regions (cf.…”
Section: Observations Of Whistler-mode Chorus and Hiss Emissionmentioning
confidence: 99%